2020
DOI: 10.1128/aem.00808-20
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Metabolic Flexibility of “ Candidatus Accumulibacter phosphatis” through Redox Cofactor Analysis and Metabolic Network Modeling

Abstract: Environmental fluctuations in the availability of nutrients lead to intricate metabolic strategies. Candidatus Accumulibacter phosphatis, a polyphosphate accumulating organism (PAO) responsible for enhanced biological phosphorus removal (EBPR) from wastewater treatment systems, is prevalent in aerobic/anaerobic environments. While the overall metabolic traits of these bacteria are well described, the non-availability of isolates has led to controversial conclusions on the metabolic pathways used. Here, we expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 82 publications
1
28
0
Order By: Relevance
“…Accumulibacter’s anaerobic metabolism has also been shown to differ under varying substrate or stoichiometric conditions and possibly between the two Accumulibacter types. From recent simulations of ‘omics datasets paired with enzymatic assays, the routes of anaerobic metabolism for Accumulibacter may differ based on environmental conditions (83). Under high acetate conditions, polyphosphate accumulation arises through the glyoxylate shunt, whereas under increased glycogen concentrations, glycolysis is used in conjunction with the reductive branch of the TCA cycle (83).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulibacter’s anaerobic metabolism has also been shown to differ under varying substrate or stoichiometric conditions and possibly between the two Accumulibacter types. From recent simulations of ‘omics datasets paired with enzymatic assays, the routes of anaerobic metabolism for Accumulibacter may differ based on environmental conditions (83). Under high acetate conditions, polyphosphate accumulation arises through the glyoxylate shunt, whereas under increased glycogen concentrations, glycolysis is used in conjunction with the reductive branch of the TCA cycle (83).…”
Section: Discussionmentioning
confidence: 99%
“…From recent simulations of ‘omics datasets paired with enzymatic assays, the routes of anaerobic metabolism for Accumulibacter may differ based on environmental conditions (83). Under high acetate conditions, polyphosphate accumulation arises through the glyoxylate shunt, whereas under increased glycogen concentrations, glycolysis is used in conjunction with the reductive branch of the TCA cycle (83). Furthermore, Welles et al found that Type II Accumulibacter is able to switch to partial glycogen degradation more quickly than Type I, enabling Type II to fuel VFA uptake in polyphosphate-limited conditions (84, 85).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulibacter” (approx. 95%, by proteomic investigations (Kleikamp et al 2020b) and by FISH staining (Guedes da Silva et al 2018)). Sialic acid-specific lectin staining displayed that sialic acids with α-2,3- and α-2,6-linkage to the sub-terminal monosaccharide were distributed widely on the cell surface of “ Ca .…”
Section: Discussionmentioning
confidence: 99%
“…Accumulibacter” has been identified as the dominant organisms responsible for EBPR (Zilles et al 2002). This microorganism has been well studied in the past decades: different genomic, proteomic, metabolic and modelling studies are available (Oehmen et al 2010; Barr et al 2016; Oyserman et al 2016; Guedes da Silva et al 2018; Guedes da Silva et al 2019; Rubio-Rincón et al 2019). However, most of the studies overlook the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation